Contextualizing E-Learning Experiences With Indigenous Communities: A Practical, Research-Based Approach - Joseph Levitan; Jessica Perez; Andrea Velasquez; Sulem Bello; Juan Loayza; Rosa Espinoza; Daniel Zuñiga; Gerson Candela; Juan Huertas; Cesar Cáceres; Carlos Torres; Kayla M. Johnson (International Review of Research in Open and Distributed Learning)
During the COVID-19 pandemic, more than 300,000 students in Peru dropped out of the school system. Most of the students were rural Indigenous students. A lack of infrastructure and connectivity, as well as a lack of contextualized and appropriate educational resources, made it virtually impossible for rural students to engage in formal learning. The pandemic has made clear the need and viability for distributed e-learning in rural communities. However, creating e-learning content that is contextualized to support vulnerable students’ learning has been a challenge. Little to no research has discussed how to contextualize e-learning to address both its promises and challenges. In this research note, we discuss an initiative to bring together advances in contextualized learning and e-learning to address problems with access to quality materials and curriculum in rural Peruvian schools. We highlight how interdisciplinary collaborations can support innovations and improve educational access for low-income students from remote regions through distributed learning. While research have found significant promise in contextualized education, the processes of engaging in contextualized digital learning and in low-income communities have proven difficult to implement. We discuss the concepts, research base, processes, and technology required to address these needs, as well as the curricular and pedagogical approach we take in this initiative.